Sodium alginate hydrogel dressing with high water absorption rate and application

Through sodium alginate hydrogel dressings combining sodium alginate with zinc hyaluronate and other components of sodium alginate, the absorption difficulties and infection risks of existing hydrogel dressings when treating irregular wounds are solved, and the problem of absorption difficulties and infection risks of existing hydrogel dressings is achieved. Efficient wound moisturization and healing effect.

CN119139537APending Publication Date: 2024-12-17BEIJING AEGLESSTEM TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411139596.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing hydrogel dressings are difficult to effectively absorb high exudate and increase the risk of infection when dealing with irregular wounds, and are difficult to use, and are difficult to customize shapes and sizes.

Method used

The principle of collagenizing sodium alginate and calcium ions is adopted, combined with zinc hyaluronate, carbomer 941 and poloxamer, to prepare a highly absorbent sodium alginate hydrogel dressing with a moisturizing rate of more than 86% and The swelling rate of more than 4000% can be customized according to the shape and size of the wound surface, and is easy to make.

Benefits of technology

It achieves efficient absorption of wound effusion, maintains a moist environment on the wound, promotes healing, and reduces the risk of infection, and is non-cytotoxic, suitable for care for irregular wounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a high-water-absorption sodium alginate hydrogel dressing which is composed of a solution A and a solution B. The solution A is a sodium alginate solution, and the solution B is a calcium ion solution which comprises poloxamer, zinc hyaluronate and carbomer 941. The mass concentration range of the sodium alginate solution is 1%-7%, and the concentration range of the calcium ion solution is 100-400 mM; the volume ratio of the solution A to the solution B is (1: 2)-(3: 1). The smooth and transparent moist dressing can be rapidly obtained, the dressing can be customized according to the shape and size of a wound, the moisture retention rate is 86% or above, the swelling rate is 4000% or above, wound seepage can be absorbed, the moist environment of the wound is kept, and therefore wound healing is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biotechnology, and in particular to a sodium alginate hydrogel dressing with high water absorption rate and application thereof. Background Art

[0002] Irregular wounds may be caused by trauma, diabetes, ulcers, and burns. The care of these irregular wounds faces some difficulties. For example, most existing dressings are of regular shapes or sizes, which cannot completely cover and protect irregular wounds. Irregular wounds may have exudate accumulation, especially those with cavities or pockets, which may lead to wound maceration and potential infection. In addition, since irregular wounds may have difficult-to-clean areas, which increases the risk of infection, special attention should be paid to wound cleaning and disinfection. In addition, the care of irregular wounds may require more types of dressings and more frequent changes, which may lead to increased treatment costs. In view of these problems, it is particularly important to choose dressings with appropriate customizable shapes and sizes.

[0003] In 1962, George Winter proposed that moist wounds heal faster than dry wounds. Fluid absorption by exudative wounds is an important factor affecting wound healing. Keeping the wound moist helps the healing process. The beneficial effect of a moist wound environment is to prevent tissue or cell death due to dehydration and accelerate angiogenesis. The basic principle is that an appropriate amount of exudate can provide an environment that stimulates healing by providing a series of cells and cytokines necessary for wound repair. Dermal tissue exposed to air will dehydrate, and the epidermis will migrate under the dehydrated tissue, where it can obtain enough water to survive. If a moist wound dressing is used to keep the wound surface moist, the epidermis will quickly migrate to the surface of the dermis, thereby accelerating wound healing.

[0004] Although existing hydrogel dressings have advantages in many aspects, such as keeping wounds moist and promoting healing, they also have some disadvantages. For example, the swelling rate is low, and for wounds with high exudation, they may not be able to effectively absorb a large amount of exudate. If the dressing is not changed frequently enough or the dressing is contaminated, the risk of wound infection may increase. In addition, hydrogel dressings may require more delicate operations to ensure correct application, which may increase the difficulty of use, and may require specific storage and transportation conditions to maintain their physical and chemical properties. These increase the difficulty of using hydrogel dressings, so making hydrogel dressings with higher swelling rates, controllable shapes, and simple production is a key problem that needs to be solved urgently.

[0005] Sodium alginate is widely used as a gelling agent because it can form gels with divalent cations such as calcium under mild conditions. Sodium alginate is first dissolved in water to form a solution containing sodium ions and alginate. When a solution containing calcium ions is added to the solution, the calcium ions exchange ions with the carboxyl groups in the alginate, replacing the sodium ions in the alginate. The calcium ions form strong ionic bonds with the carboxyl groups of the alginate, resulting in cross-linking between the molecular chains of sodium alginate. This cross-linking rapidly increases the viscosity of the solution and forms a three-dimensional network structure. As more calcium ions bind to the alginate, the three-dimensional network structure formed becomes more stable, eventually forming gel blocks or beads with a certain mechanical strength. Calcium alginate gels are currently used in wound dressings, dental impression materials, controlled-release drug delivery systems, and encapsulation of living cells. In recent years, alginate has been used in the wound management industry as a unique material for the development of "wet healing" products, such as skin gels, ointments, foams, and fiber non-woven dressings, which can be used to protect chronic wounds.

[0006] However, how to obtain wound dressings with high retention rate, high swelling rate and customizable shape and size remains the goal pursued by many researchers. Summary of the invention

[0007] The invention provides a sodium alginate hydrogel dressing with high water absorption rate. The dressing utilizes the gelling principle of sodium alginate and calcium ions, and adds components such as zinc hyaluronate, carbomer 941, and poloxamer during the manufacturing process, so as to quickly obtain a smooth and transparent moist dressing. The dressing can not only be customized according to the shape and size of the wound, but also has a moisture retention rate of more than 86% and a swelling rate of more than 4000%, and can absorb wound exudate, maintain a moist environment for the wound, and thus promote wound healing.

[0008] On one hand, the present invention provides a sodium alginate hydrogel dressing with high water absorption rate, which consists of two parts, solution A and solution B, wherein solution A is a sodium alginate solution, and solution B is a calcium ion solution comprising poloxamer, zinc hyaluronate, and carbomer 941; the mass concentration range of the sodium alginate solution is 1%-7%, and the concentration range of the calcium ion solution is 100-400mM; the volume ratio of solution A to solution B is 1:2-3:1.

[0009] In some embodiments, the volume ratio of solution A and solution B is 1:2, 1:1, 3:2, 1:2, 5:2, 3:1, the more optimal range of volume ratio is 1:1-3:1, and the optimal ratio is 2:1.

[0010] In some embodiments, the optional mass concentration range of sodium alginate in the solution A is 3%-6%, and the optimal concentration is 5%.

[0011] In some embodiments, in the solution B, the concentration of calcium ions ranges from 100mM, 110mM, 120mM, 130mM, 140mM, 150mM, 160mM, 170mM, 180mM, 190mM, 200mM, 210mM, 220mM, 230mM, 240mM, 250mM, 260mM, 270mM, 280mM, 290mM, 300mM, 310mM, 320mM, 330mM, 340mM, 350mM, 360mM, 370mM, 380mM, 390mM, and 400mM, with 200mM being the optimal choice.

[0012] The calcium ion solution is a solution formed by dissolving a soluble calcium salt in sterile water for injection (physiological saline, phosphate buffer solution, etc. may also be used), and the soluble calcium salt includes one or more of calcium chloride, calcium bromide, calcium nitrate, calcium chlorate, calcium perchlorate, calcium bicarbonate, and calcium dihydrogen phosphate. Preferably, the soluble calcium salt is calcium chloride.

[0013] In some embodiments, the concentration of carbomer 941 in solution B ranges from 1% to 3%, with the optimal concentration being 2%; the concentration of poloxamer ranges from 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, and 30%, with the optimal concentration being 20%; and the concentration of zinc hyaluronate is 0.2%.

[0014] Zinc hyaluronate is the zinc salt form of hyaluronic acid, which can greatly improve the absorption rate of hyaluronic acid in the human body compared with sodium hyaluronate. Zinc hyaluronate has a strong moisturizing effect and can combine more than 400 times of its own weight of water. In addition, zinc hyaluronate also has antioxidant and soothing effects. A trace amount of zinc hyaluronate (Huaxi Biology) is added to the B component of the present invention. The general amount used in this area is less than 0.5%. Since the absorption rate of the components is not greatly affected within this range, the present invention selects a commonly used antibacterial moisturizing dosage of 0.2%. Carbomer 941 is a polymer commonly used in personal care products and pharmaceutical preparations, which can reduce the loss of moisture and nutrients in the skin, delay skin aging, and has an anti-inflammatory effect, can improve the skin redness and local swelling caused by improper cleaning or inflammatory stimulation, in addition, carbomer 941 also has a bactericidal effect, and can improve the skin redness and local swelling caused by improper cleaning or inflammatory stimulation. Poloxamer is a non-ionic block copolymer widely used in medicine and cosmetics. It can increase skin permeability and promote the absorption of topical medications. Poloxamer hydrogel is temperature-sensitive and can be used to prepare thermosensitive sustained-release and controlled-release preparations, such as long-acting injections and long-acting eye drops.

[0015] In some embodiments, the solution B also includes silver ions such as silver carbonate, 1,2-hexanediol, and glycerol to further moisturize and preserve, and additional additives such as therapeutic chemical and cellular drugs can be added.

[0016] Silver has been used to kill harmful bacteria by destroying cell membranes and interfering with the activity of bacterial enzymes. Silver ions are non-toxic to the human body and can create a sterile environment even at low concentrations. 0.25% silver ions have antibacterial activity against both Gram-positive and Gram-negative bacteria. The present invention finally uses silver carbonate (Aladdin, S104735) with a commonly used antibacterial dose of 0.05%. 1,2-Hexanediol has multiple effects in cosmetics and personal care products. It combines with moisture on the skin to form a molecular film, helps lock in moisture, maintains skin moisture levels, and has a certain antibacterial effect. The present invention uses 1,2-hexanediol (Aladdin, H108067) at a commonly used dose of 3%. Glycerin (propylene glycol) is a polyol widely used in cosmetics and personal care products. It is a powerful moisturizer that helps the skin retain moisture and avoids dryness. In addition, glycerin may have a slight anti-inflammatory effect and help reduce skin inflammation. Among pharmaceutical excipients, the maximum amount of glycerol (Aladdin, G116203) for topical application can reach 50%. Considering the fluidity and safety of component B, the present invention finally selects 2%.

[0017] Another aspect of the present invention provides the use of the sodium alginate hydrogel dressing in wound healing, such as burns, scalds or other open wounds. During use, first apply solution A to the wound surface to any shape, then apply solution B to the surface of A, wait for 10 seconds or more, and then completely peel off the gel dressing to obtain a hydrogel dressing with a smooth, transparent surface and self-defined shape.

[0018] The technical solution of the present invention has the following beneficial effects:

[0019] 1. The sodium alginate gel dressing of the present invention can be customized into gel dressings of different shapes and sizes according to the needs of the wound surface.

[0020] 2. The sodium alginate gel dressing of the present invention has no cytotoxicity.

[0021] 3. The sodium alginate gel dressing of the present invention has a swelling rate of more than 4000%, and can absorb excess exudate around the wound tissue.

[0022] 4. The sodium alginate gel dressing of the present invention has an equilibrium moisture content of more than 97% and a moisture retention rate of more than 86% at 37°C, which maintains a moist environment and is beneficial to wound healing.

[0023] 5. The sodium alginate gel dressing of the present invention can increase the moisture content of the skin by 29% and has excellent skin moisturizing properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A diagram showing the gel formation of alginate gel dressing.

[0025] Figure 2 A schematic diagram of a single layer of gel dressing (black box in the middle left) and an irregular schematic diagram (black box in the middle right) are shown.

[0026] Figure 3 A graph showing cell viability of the gel dressing NRU assay is shown.

[0027] Figure 4 The weight change curve of the sodium alginate film over time is shown.

[0028] Figure 5 The graph shows the weight change curve of the sodium alginate dry film during water absorption.

[0029] Figure 6 The figure shows the comparison of skin moisture changes after application of sodium alginate dressing and commercially available dressing. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0031] The reagents used in the following examples are as follows: sodium alginate, Aladdin, S100126, viscosity 200±20 mPa.s; calcium chloride, Solebol, G0070; carbomer 941, Xinrunde, cas9003-01-4; poloxamer, Aladdin, P434419; sodium alginate, Aladdin, S100126, viscosity 200±20 mPa.s.

[0032] Unless otherwise specified, all experimental methods were conventional methods.

[0033] Other materials and reagents used, unless otherwise specified, can be obtained from commercial sources.

[0034] Example 1 Exploration of the concentration of sodium alginate in component A of solution

[0035] Prepare a sodium alginate solution with a mass concentration of 0.5%-7% and a 100mM calcium chloride solution respectively. Spread 1mL of the sodium alginate solution on the bottom of a culture dish, add 0.5mL of the calcium chloride solution, stir, and observe the gelation state and gelation time.

[0036] The cross-linking time is the time it takes for the material structure to change, that is, the time it takes to change from a solution state to a sol state. Considering the use scenarios of gel dressings, a time shorter than 10 seconds will increase the difficulty of actual use, and a time too long will increase the risk of wound exposure, so a gelling time of 10-20 seconds is more conducive to the use of dressings on wounds. In addition, 8% sodium alginate is difficult to dissolve, so it will no longer be optimized for use in the future.

[0037] The experimental results are shown in Table 1. Based on the experimental results, it is determined that the optional concentration range of sodium alginate in the final gel dressing product is 1%-7%, the suboptimal range is 3%-6%, the more preferred range is 4%-6%, and the optimal range is 5%.

[0038] Table 1: Sodium alginate concentration exploration experiment record

[0039]

[0040] Example 2 Solution B core component concentration exploration test

[0041] The concentrations of carbomer 941, calcium chloride, poloxamer in component B and sodium alginate in component A play an important role in the gel formation rate and gel state of the gel dressing, so it is necessary to explore their appropriate concentrations through experiments.

[0042] The standard orthogonal table 16.4.4 was used to carry out the orthogonal experimental design in Table 2 to prepare calcium ion solution and sodium alginate solution. The sodium alginate solution was prepared by dissolving water, and the other components in the calcium ion solution were glycerol, zinc hyaluronate, silver carbonate and 1,2-hexanediol.

[0043] Take 2mL of sodium alginate solution and apply it on the skin, with an area of ​​about 6cm*6cm and a thickness of 2mm. Take 1mL of calcium ion solution and spread it on the sodium alginate, observe the gelation time, removal state and uniformity of each component, and finally determine the parameters of moderate gelation reaction time (10 seconds), easy removal of the dressing and smooth and uniform surface.

[0044] According to the test results, the range of sodium alginate in component A is 4%-6%, and the optimal choice is 5%. The range of calcium chloride concentration in component B is 100-400mM, and the optimal choice is 200mM. The range of carbomer 941 concentration in component B is 1%-3%, and the optimal choice is 2%. The range of poloxamer concentration in component B is 10%-30%, and the optimal choice is 20%.

[0045] Table 2: Orthogonal experimental design table

[0046]

[0047] Example 3 A, B colloid ratio exploration test

[0048] After exploring the optimal range of components A and B, the final exploratory experiment was conducted on the gelling reaction ratio and method. According to the optimal formula of components A and B, components A and B were prepared, and the gelling reaction was carried out at different volume ratios as shown in Table 3. The gelling state and gelling time were observed, and the results are shown in Table 3.

[0049] According to the test results, the ratio of component A to component B is in the range of 1:2-3:1, the better range is 1:1-3:1, and the optimal ratio is 2:1.

[0050] Table 3: A and B group allocation ratio exploration experiment record

[0051]

[0052] Example 4 Preparation of Sodium Alginate Hydrogel Dressing

[0053] The component A used in this example is a sodium alginate solution, and the basic solvent is sterile water for injection. 40 mL of sterile water for injection is taken into a 50 mL centrifuge tube, 2 g of sodium alginate is weighed and added to the liquid surface of the centrifuge tube and shaken vigorously to make the sodium alginate evenly distributed, and shaken at room temperature overnight to make it fully swell to obtain a 5% sodium alginate solution.

[0054] The component B used in this embodiment is a calcium ion solution, the basic solvent is a calcium chloride solution and water, and the final concentration of the component formula is shown in Table 4:

[0055] Table 4: Final concentration formula of calcium ion solution

[0056] Serial number Reagents concentration 1 Calcium chloride 200mM 2 Carbomer 941 2%(w / v) 3 Poloxamer 20%(w / v) 4 glycerin 2%(v / v) 5 Zinc Hyaluronate 0.2%(w / v) 6 Silver carbonate 0.05%(w / v) 7 1,2-Hexanediol 3%(v / v)

[0057] Take 1mL of component A and 0.5mL of component B and add them to a glass bottle. After mixing for 10 seconds, cross-linking occurs and the solution turns into a gel state. Invert the glass bottle and you can see that the gel is adsorbed on the bottom of the bottle without flowing. Figure 1 The film can be completely removed and is smooth, transparent, and has a uniform texture. After the film is removed, no liquid remains at the bottom of the bottle.

[0058] Example 5 Application of the sodium alginate hydrogel dressing prepared in Example 4

[0059] Prepare component A and component B according to the conditions of Example 4, take 1 mL of component A and apply it on the skin, with an area of ​​3 cm*3 cm and a thickness of 2 mm. Take 0.5 mL of component B solution and spread it on component A. After standing for 10 seconds, the gel dressing can be completely peeled off from the edge to obtain a clear and smooth gel dressing, such as Figure 2As shown in the black dotted box in the left figure. In addition, the shape of the dressing can be controlled by component A, and can be freely applied and fixed into any shape and size according to the actual needs of the wound, such as Figure 2 As shown in the picture on the right.

[0060] Example 6 Toxicity Test

[0061] The cytotoxicity test of gel dressing was carried out with reference to Part 5: In vitro cytotoxicity test of "Biological Evaluation of Medical Devices" GB / T16886.

[0062] According to the conditions and methods of Example 5, a clear and smooth gel dressing was obtained, and four parallels were set in each group. The dressing was placed in a clean bench and sterilized by ultraviolet irradiation, 30 minutes on each side, and all operations were strictly sterile.

[0063] The gel dressing was incubated in culture medium (α-MEM+10% fetal bovine serum, C12571500BT, C0235) at a mass volume ratio of 1 g:15 ml. After stirring at 100 rpm for 24 hours, the supernatant was pipetted into a new sterile tube and stored at 4°C for later use.

[0064] The cell lines used in the toxicity test mentioned in Part 5 of GB / T16886 can be tested with conventional commercially available cells, such as human umbilical vein endothelial cells (HUVEC), human renal epithelial cells (293T) and human breast cancer cells (MCF-7). It is preferred to use established cell lines and obtain them from approved storage sources. The cell line used in the present invention is HUVEC. The specific steps of the experiment are to take HUVEC cells in normal growth state, pass them for 3 times, and prepare 1×10 5 Use a multichannel pipette to add 100 μL of culture medium to the outer wells of the 96-well plate (blank), and add 100 μL of a cell suspension with a density of 1×10 cells / mL to the remaining wells. 5 cells / mL of cell suspension (1×10 4 Another plate was prepared for positive control (sodium dodecyl sulfate SLS, CAS151-21-3, 0.093 mg / mL). The cells were cultured for 24 h (5% CO 2 , 37°C, >90% humidity) to form a semi-confluent monolayer. During this incubation period, cells were allowed to recover, attach, and grow exponentially. Each plate was checked under a phase contrast microscope to ensure that the cell growth in each well of the microtiter plate was relatively equal.

[0065] After 24 h of culture, the culture medium was aspirated. 100 μL of the treatment medium containing the gel dressing extract and SLS solution was added to each well. The cells were cultured for 24 h and 48 h (5% CO 2 The cytotoxicity of the gel dressings was analyzed using the NRU assay after incubation at 4 °C (37 °C, >90% humidity).

[0066] The NRU assay was based on the method provided by Ellen Borenfreund. Neutral red uptake into lysosomes and vacuoles of live cells is used to quantify cell number and activity. Wash cells with 100 μL of pre-warmed PBS and gently tap to remove the wash solution. Add 100 μL of NR medium and incubate at 37°C in a humidified atmosphere of 5% CO. 2 Incubate in air for 3 hours. After incubation, remove the NR medium and wash the cells with 150 μL PBS. After removing the PBS, add 150 μL NR eluent to all wells, including the blank. Place the microtiter plate on a shaker and shake rapidly for 10 minutes until NI is extracted from the cells and a uniform solution is formed. Use a microtiter plate photometer to measure the absorbance of the color development solution at 540 nm with the blank as reference. Plot the cell viability results as a percentage of the control. The results are shown in Figure 3 As shown, the gel dressing had no cytotoxicity at 24 hours and 48 hours, indicating that the dressing would not have a toxic effect on wound cells within 48 hours of use.

[0067] Example 7 Water absorption test

[0068] Component A and component B were prepared according to the conditions of Example 5, and 2 mL of component A solution was applied to the skin, with an area of ​​6 cm*6 cm and a thickness of 2 mm. 1 mL of component B solution was spread on component A, and after standing for about 10 seconds, the dressing could be completely peeled off from the edge to obtain a clear and smooth gel dressing.

[0069] Use absorbent paper to absorb excess moisture from the surface, place it on a scale and weigh it, and record the initial weight of the dressing. Spread the dressing flat in a culture dish and place it in a 60°C forced air drying oven. Measure the weight every 5 minutes until the weight remains stable, and record the weight change of the dressing. Soak the dry dressing in 25°C saline, take it out at different time points, use absorbent paper to absorb excess moisture from the surface, and then weigh it, and record the weight change of the dressing. Use Graphdprism to statistically analyze the weight change of the dressing. The weight change of the gel dressing in the drying oven over time is shown in the figure. Figure 4 As shown in the figure, after 2 hours, the weight of the dressing remained stable, and the texture of the final dressing was similar to hard plastic. The dried gel dressing obtained above was further placed in physiological saline, and the weight of the dried gel dressing changed with time during the water absorption process as shown in the figure. Figure 5 As shown in the figure, after 45 minutes, the weight of the dressing remained stable, indicating that the dressing has good water retention and water absorption properties, can quickly absorb wound exudate during actual use, and can maintain a moist environment in the wound, which is beneficial to the subsequent recovery of the wound.

[0070] Example 8 Swelling Rate Test

[0071] According to the conditions and methods of Example 5, a clear and smooth gel dressing was obtained, and four parallel groups were set up in each group.

[0072] Use absorbent paper to absorb excess moisture on the surface, place it on a balance and weigh it, and record the initial weight of the dressing m0. Spread the dressing flat in a culture dish and place it in a 60°C forced air drying oven. Measure the weight every 10 minutes until the weight remains stable, and record the dry weight of the dressing m1. Soak the dry dressing in 25°C saline for 10 minutes, use absorbent paper to absorb excess moisture on the surface and weigh it, and record the saturated weight of the dressing m2. Spread the saturated film flat in a culture dish and place it in a 37-degree constant temperature box. After 30 minutes, take it out and measure the weight of the dressing m3. Calculate the swelling rate, equilibrium water content and moisture retention rate of the sodium alginate gel dressing according to the following formulas:

[0073] Swelling rate = (saturated weight m2-dry weight m1) / dry weight m1*100%

[0074] Equilibrium moisture content = (saturated weight m2-dry weight m1) / saturated weight m2*100%

[0075] Moisture retention rate = 100 - water loss rate = 100 - [(saturated weight m2-m3) / saturated weight m2*100%]

[0076] The experimental results are shown in the following table:

[0077] Table 5: Gel dressing quality changes and analysis results

[0078] Group 1 2 3 4 Dish weight 9.826 9.940 9.822 7.182 Dressing weight m0 0.444 0.387 0.408 0.414 Dressing + dish 10.267 10.324 10.235 7.588 10min 9.876 9.978 9.926 7.253 20min 9.843 9.956 9.835 7.196 30min 9.841 9.956 9.835 7.194 40min 9.840 9.955 9.835 7.194 Dressing dry weight m1 0.014 0.015 0.013 0.012 Saturated weight m2 0.688 0.617 0.558 0.603 37℃Weight m3 0.601 0.535 0.497 0.544 Swelling rate (%) 4814.29 4013.33 4192.31 4925.00 Equilibrium moisture content (%) 97.97 97.57 97.67 98.01 Moisture retention after 30 minutes (%) 87.35 86.71 89.07 90.22

[0079] The results showed that the sodium alginate gel dressing has a swelling rate of more than 4000%, can absorb excess exudate around the wound tissue, and has a balanced water content of more than 97% and a moisture retention of more than 86%. It can maintain a moist environment in the wound and promote wound healing.

[0080] Example 9 Skin Test

[0081] 30 healthy female volunteers aged 20-35 were selected and randomly divided into two groups (no other cosmetics were used 72 hours before the experiment), 15 people in each group, and tried the gel dressing obtained in Example 5 and the commercially available moisturizing gel dressing respectively. The volunteers rested for 30 minutes in a room at 26 degrees Celsius and 50% relative humidity. The skin moisture and oil status were measured using a skin tester, and the initial status was recorded. The sodium alginate gel dressing and the commercially available dressing samples were covered on the inner side of the right forearm of the volunteers, the dressing was removed after 15 minutes, and the skin moisture and oil status of the skin were measured using a skin tester at 15 minutes, 30 minutes, 60 minutes and 120 minutes, respectively. The test was repeated 3 times each time to obtain the detection average value.

[0082] The results of the sodium alginate dressing skin measurements are shown in Table 6:

[0083] Table 6: Changes in skin moisture and oil content of volunteers wearing sodium alginate dressing at different times

[0084]

[0085] The skin measurement results of commercially available dressings are shown in Table 7:

[0086] Table 7: Changes in skin moisture and oil content of volunteers wearing commercially available dressings at different times

[0087]

[0088] The moisture change rate of sodium alginate dressings and commercially available dressings 15 minutes and 120 minutes after application was statistically analyzed. 15 minutes after application, the moisture content of the sodium alginate dressing group increased by 28.8±2.7%, and the moisture content of the commercially available dressing increased by 16.9±1.1%. The T test was performed using Graphd Prism, and the P value between the two groups was 0.0007, indicating a significant difference. 120 minutes after the dressing was removed, the moisture content of the sodium alginate mask group increased by 9.3±1.3%, and the moisture content of the commercially available dressing increased by 2.9±0.5%. The P value between the two groups was 0.0004, indicating a significant difference. The results are as follows Figure 6 As shown, the moisturizing property of sodium alginate dressing on the skin is significantly higher than that of commercially available dressings.

[0089] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A sodium alginate hydrogel dressing with high water absorption, characterized in that: It consists of two parts, solution A and solution B. Solution A is a sodium alginate solution, and solution B is a calcium ion solution containing poloxamer, zinc hyaluronate, and carbomer 941. The mass concentration range of the sodium alginate solution is 1%-7%, and the concentration range of the calcium ion solution is 100-400mM. The volume ratio of solution A to solution B is 1:2-3:

1.

2. The sodium alginate hydrogel dressing according to claim 1, characterized in that: The volume ratio of solution A to solution B is 1:1-3:

1.

3. The sodium alginate hydrogel dressing according to claim 2, characterized in that: The volume ratio of solution A to solution B is 2:

1.

4. The sodium alginate hydrogel dressing according to claim 1, characterized in that: The mass concentration of sodium alginate in the solution A is in the range of 3% to 6%.

5. The sodium alginate hydrogel dressing according to claim 1, characterized in that: The concentration range of the calcium ion solution is 200 mM.

6. The sodium alginate hydrogel dressing according to claim 1, characterized in that: The mass concentration of carbomer 941 in the solution B is in the range of 1%-3%, the mass concentration of poloxamer is in the range of 10%-30%, and the mass concentration of zinc hyaluronate is 0.2%.

7. The sodium alginate hydrogel dressing according to claim 6, characterized in that: In the solution B, the mass concentration of carbomer 941 is 2%, the mass concentration of poloxamer is 20%, and the mass concentration of zinc hyaluronate is 0.2%.

8. The sodium alginate hydrogel dressing according to claim 1, characterized in that: The solution B also includes silver carbonate, 1,2-hexanediol and glycerol.

9. The sodium alginate hydrogel dressing according to claim 8, characterized in that: The volume ratio of solution A to solution B is 2:1; the mass concentration of sodium alginate in solution A is 5%, and in solution B, the concentration of calcium ions is 200 mM, the mass concentration of carbomer 941 is 2%, the mass concentration of poloxamer is 20%, the mass concentration of zinc hyaluronate is 0.2%, the mass concentration of silver carbonate is 0.05%, the volume ratio of 1,2-hexanediol is 3%, and the volume ratio of glycerol is 2%.

10. Use of the sodium alginate hydrogel dressing according to any one of claims 1 to 9 in preparing a wound healing material or a medicine.

Citation Information

Cited By

  • Alginate dressing and preparation method thereof

    CN120053743A

  • Hydrogen-loaded material wound repair patch and preparation method thereof

    CN121695315A